Ferramenta para monitoramento de dispositivos de rede implementada utilizando a linguagem de programação Python - Ramos, Johny de Souza (2022)
Computer networks are increasingly present in all organizations, whether public or private. Along with this increase, it is increasingly necessary to use tools to control and monitor these networks. Only in this way is it possible to identify operational and safety failures before they cause damage to the company. The objective of this work is to bring a practical approach to the development of a basically network monitoring tool, making use mainly of the SNMP protocol for communication and the Python programming language that was chosen to be used in this project due to its wide use and content made available by the community.